Endometriosis: diagnóstico clínico - Negrón Rodríguez, José (2026)
Endometriosis is a inflammatory chronic systemic disease that can cause pain,infertility and reduced quality of life. Diagnosing endometriosis remains challenging, which yields diagnostic delays for patients. There are no characteristic or pathognomonic symptoms of endometriosis; however, the association of specific symptoms increases the likelihood of diagnosing the disease. Dysmenorrhea,dyspareunia, dyschezia, dysuria, chronic pelvic pain, and infertility are all associated with endometriosis. Physical examination allows us to detect endometriosis by visualization or palpation, assessing pain sites and pelvic organ mobility. Currently, there are no specific biomarkers for endometriosis. Ultrasound (TV) and magneticresonance imaging (MRI) are important tools to aid in the diagnosis and spread of disease. Definitive diagnosis requires histological confirmation of the excised tissue, obtained through surgery, preferably minimally invasive surgery, either laparoscopic or robotic.